2009
DOI: 10.1111/j.1095-8649.2009.02282.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive characteristics and population decline of four species of skate (Rajidae) off the eastern coast of Canada

Abstract: Four of the most common species of skate (Rajidae) were studied off eastern Canada to determine if their reproductive characteristics were linked to their population trajectories. The fecundity of the winter skate Leucoraja ocellata, the little skate Leucoraja erinacea, the thorny skate Amblyraja radiata and the smooth skate Malacoraja senta averaged between 41 and 56 egg cases per year for each species. For all species but L. ocellata, males matured at larger sizes and at later ages than females. Theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…Studies on other species of the family Arhynchobatidae (Fowler, 1934) demonstrated that the total clasper length and clasper gland length fitted a sigmoid growth curve, at least in the genus Atlantoraja and Rioraja agassizi (Oddone & Vooren 2005;Oddone et al, 2007a;.This type of logistic growth curves were also observed in four species of the family Rajidae (Blainville, 1816), namely, Leucoraja ocellata (Mitchill, 1815), Leucoraja erinacea (Mitchill, 1825), Amblyraja radiata (Donovan, 1808) and Malacoraja senta (Garman, 1885), distributed off the east coast of Canada (McPhie & Campana, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…Studies on other species of the family Arhynchobatidae (Fowler, 1934) demonstrated that the total clasper length and clasper gland length fitted a sigmoid growth curve, at least in the genus Atlantoraja and Rioraja agassizi (Oddone & Vooren 2005;Oddone et al, 2007a;.This type of logistic growth curves were also observed in four species of the family Rajidae (Blainville, 1816), namely, Leucoraja ocellata (Mitchill, 1815), Leucoraja erinacea (Mitchill, 1825), Amblyraja radiata (Donovan, 1808) and Malacoraja senta (Garman, 1885), distributed off the east coast of Canada (McPhie & Campana, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…These results indicate that the nature of potential shifts in community structure of skates will not be easily predicted by body size, as has been argued for the North Atlantic skate assemblage [66]. For the eastern Scotian Shelf skate assemblage, McPhie and Campana [5] found that the species with the highest ratios of age at maturity to maximum age had the lowest predicted population growth rates, and that this was a better predictor of population growth rate than was body size. Including the species analyzed here, data for high-latitude skates supports the ratio between age at maturity and longevity as the best indicator of population growth rate (Figs.…”
Section: Discussionmentioning
confidence: 66%
“…Of these taxa, it could be argued that skates have received the least research attention. However, concern for the appropriate management of skates has increased in the last decade as declines of skate populations have been detected in response to both direct and indirect fishing pressure [2], [3], [4], [5]. The emerging body of literature on skates indicates that species vary widely in life-history traits [6], which further complicates the assessment and management of mixed-species fisheries and highlights the need for species-specific data.…”
Section: Introductionmentioning
confidence: 99%
“…There is no reason that this inattention need occur -the predictable fecundity and external sex characteristics of elasmobranchs should make them at least as easy to manage as teleost stocks -but the track record for shark management worldwide has been poor (Dulvy et al 2008). Are transboundary shark populations destined to go the way of their far less charismatic elasmobranch cousins, the skates and rays, whose population numbers have declined by over 90% in some regions (Shepherd and Myers 2005;McPhie and Campana 2009)? In this perspective, I will argue that shark life history characteristics and their transboundary migratory habits put them at greater risk from fishing pressure than possibly any other group of fishes in the North Atlantic.…”
Section: Introductionmentioning
confidence: 99%